42.1k views
1 vote
The question is ab+c=d solve for b

User XZVASFD
by
4.9k points

2 Answers

4 votes

Answer:

b =
(d-c)/(a)

Explanation:

Given

ab + c = d ( subtract c from both sides )

ab = d - c ( divide both sides by a )

b =
(d-c)/(a)

User Pee
by
6.1k points
5 votes

Answer:

b = (d - c)/a

Explanation:

ab + c = d

ab = d - c

b = (d - c)/a

User David Ferretti
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.